Response of Medical Cannabis (Cannabis sativa L.) Genotypes to K Supply Under Long Photoperiod - Saloner, Avia; Sacks, Mollie M.; Bernstein, Nirit (Frontiers in Plant Science, 2019)
Potassium is involved in regulation of multiple developmental, physiological and metabolic processes in plants, including photosynthesis and water-relations. We lack information about the response of medical cannabis to mineral nutrition in general, and K in particular, which is required for development of high-grade standardized production for the medical cannabis industry. The present study investigated the involvement of K nutrition in morphological development, the plant ionome, photosynthesis and gas-exchange, water relations, water use efficiency and K use efficiency, comparatively for 2 genotypes of medical cannabis, under a long photoperiod. The plants were exposed to 5 levels of K (15, 60, 100, 175 and 240 ppm K). Growth response to K inputs varied between genotypes, revealing genetic differences within the cannabis sativa species to mineral nutrition. 15 ppm K was insufficient for optimal growth and function in both genotypes and elicited visual deficiency symptoms. 240 ppm K proved excessive and damaging to development of the genotype Royal Medic, while in Desert Queen it stimulated rather than restricted shoot and root development. The differences between the genotypes in the response to K nutrition were accompanied by some variability in uptake, transport and accumulation of nutrients. For example, higher levels of K transport from root to the shoot were apparent in Desert Queen. However, overall trends of accumulation were similar for the two genotypes demonstrating competition for uptake between K and Ca and Mg, and no effect on N and P uptake except in the K-deficiency range. The extent of accumulation was higher in the leaves>roots>stem for N, and roots>leaves>stem for P. Surprisingly, most micronutrients (Zn, Mn, Fe, Cu, Cl) tended to accumulate in the root, suggesting a compartmentation strategy for temporary storage, or for prevention of access concentrations at the shoot tissues. The sensitivity of net-photosynthetic rate, gas exchange and water use efficiency (WUE) to K supply differed as well between genotypes. The results suggest that growth reduction under the deficient supply of 15 ppm K was mostly due to impact of K availability on water-relations of the tissue and transpiration in Royal Medic, and water relations and carbon fixation in Desert Queen.